Tug1 Acts on ERK12 Signaling Pathway to Aggravate Neuronal Damage after Acute Ischemic Stroke - Chen, Xiaojie; Xie, Yuduan; Liang, Chunling; Yang, Dawei; Li, Xiaotao; Yu, Jie (Cellular and Molecular Biology, 2022)
Approximately 85% of stroke patients suffer from ischemic stroke, which has a high incidence and difficult prognosis. It has become one of the leading causes of death in middle-aged and elderly people and seriously threatens human health. This study mainly considers the role of lncRNA tug 1 on the ERK 12 signaling pathway to enhance neuronal damage after acute ischemic stroke. In the experiment, the middle cerebral artery occlusion (MCAO) model was constructed using the thread embolization method. The real-time quantitative RT-CR method was used to detect the relative transcriptional activity of TG1, GAS5 and SM22a genes in tissues. The relative expression level of SM22a protein in tissues was detected by the immune-histochemical method. Twenty-four hours after cerebral infarction, the nerve function, cerebral infarction area and ERK1/2 protein expression level of cerebral cortex on the side of cerebral infarction were detected in each group. The experimental results showed that the successful animal behavior scores of the MCAO model in the normal saline control group and Pepstatin A interference group were 1 point 25, 2 points 17 and 3 points 18. The results show that lncRNA tug1 can enhance the neuronal damage of the ERK12 signaling pathway after acute ischemic stroke. lncRNATUGl plays an important role after OGD/RX and can accelerate cell apoptosis. If the expression of lncRNATUGl is inhibited, the number of apoptosis is significantly reduced.